Geological facts, geological judgments, geological truth and the State Geological Map of the Ukrainian Shield - Gintov, Oleg; Mychak, Sergii (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2024)
The shortcomings of the Geological maps in Ukraine and maps of the minerals of the crystalline basement of the Ukrainian Shield of the State Geological Map of Ukraine (scale 1:200 000) published in Ukraine are considered in terms of their compliance with modern views on the structure and development of the Earth's crust in the Early Precambrian (Archean-Early Proterozoic). It is shown that, despite the basic requirement of the Early Precambrian Section of the National Stratigraphic Committee of Ukraine that the Precambrian formations of the Ukrainian Shield should be age-divided based mainly on isotopic geochronology, this did not become the basis for the preparation of geological maps. Some authors and editors of maps have not gotten rid of the influence of the outdated concept of the formation of early Precambrian strata by their successive layering and fixing this sequence in the vertical section of the earth's Scrust during regional metamorphism. The determining role of horizontal crustal movements, plume and plate tectonic processes was also perceived ambiguously. The role of large-scale thrusts and subductions of lithoplates, which changed the age relationships of rocks in the section, was not taken into account. The article compares tectonic schemes and sections to geological and mineral maps of the crystalline basement of the Ukrainian Shield with maps of the Precambrian basement of the South African, Canadian, and Western Australian Shields, in which the legends replace the principle of "lower-higher" with the principle of "older-younger" based on isotopic dating. It is shown how the views of Western geologists have evolved from the mid-twentieth century to the present day in the study of the Archaic Barberton Greenstone Belt (eastern margin of the Kaapvaal Craton, South Africa), which has long been building geological map legends on the basis of highly accurate isotopic data. The disadvantage of the published Geological maps and mineral maps of the crystalline basement of the Ukrainian Shield at a scale of 1:200,000 is also the presence of a large number of inconsistencies in the author's interpretation of the geological content of different, and even neighboring by nomenclature, map sheets, especially tectonic schemes and sections, and designations of the material composition of rocks. The authors of the article propose to return again to the discussion and solution by geologists and geological organizations of the issue of compiling a New series of Geological maps and mineral maps of the crystalline basement of the Ukrainian Shield at a scale of 1:200,000 on the basis of previous and new geological, geophysical and geochemical data obtained over the past 20 years and the latest achievements of world geological science. Key words: Ukrainian Shield, isotopic geochronology, geological maps, tectonic schemes, faults, tectonophysics, geological truth.